External Validation of the Difficult Intravenous Access (DIVA3) Score as a Clinical Predictive Rule for Identifying Difficult Intravenous Access in Children - Fatemeh Taghinejad; Fatemeh Hashemi; Fatemeh Mokhtari; Lida Nikfarid (Mashhad University of Medical Sciences, 2022)
Background: Intravenous catheter insertion in pediatrics is associated with pain and discomfort. DIVA3 is a pediatric clinical score rule developed to estimate failure in intravenous placement for infants and children. Aim: This study aimed to validate the external validation of DIVA 3 as a clinical predictive rule for identifying difficult intravenous access in children. Method: This prospective cross-sectional study was performed on 310 children aged less than 12 years who underwent intravenous catheter placement in the pediatric wards of two specialized pediatrics hospitals in Tehran. The DIVA 3 score was estimated and recorded by a nurse. The measured outcome was failure or success of Peripheral Intravenous (PIV) PIV cannula placement on the first attempt. The number of attempts was recorded for all cases. The failure rates were determined for all children with DIVA score of 4 and graters. The sensitivity, specificity, and positive and negative predictive values were determined considering a confidence interval (CI) of 95%. Results: Sensitivity, specificity, Positive Predictor Value, and Negative Predictive value of DIVA3 (cutoff point ≥4) were 95.9%, 84.3%, 93.8, and 84.3%, respectively (95% CI: 0.932-0.932). For 85 cases, two nurses scored the amount of success in catheterization at the same time using DIVA3 to calculate inter-rater agreement. Kappa values were between 0.52 and 0.89. Implications for Practice: The results support the importance of using DIVA3 despite the variable diagnostic value which had in numerous studies. The results emphasize the relationship between other factors and the need to consider them in the success rate prediction algorithm.